A Systematic Literature Review: The Effectiveness of Interactive E-Modules in Numeracy Learning on Students' Concept Understanding - Dewi Ayu Sinta Pratiwi; I Made Ardana; Gede Suweken (Jurnal Penelitian Pendidikan IPA, 2026)
This study systematically reviews the effectiveness of interactive e-modules in Numeracy learning to improve students' concept understanding. The study employed a Systematic Literature Review (SLR) method using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. Data were collected from 12 articles published in SINTA-indexed journals between 2021–2025. Analysis identified publication trends, educational levels, and e-module effectiveness on concept understanding. Results indicate interactive e-modules effectively improve Numeracy concept understanding, marked by significant N-Gain score improvements and learning completeness. Publication trends increased rapidly (2021–2025), dominated by Junior High School (50%), Senior High School (33%), and Elementary School (17%). The study concludes further research is needed at the Elementary level, adjusting learning models to students' developmental stages.